Keep Talking. Communicative Fluency Activities For Language Teaching - Klippel, Friederike (Cambridge Cambridge University Press, 1998)
The activities in this book have been grouped in 13 sections, according to type. Since some types of activities share certain characteristics, there is some overlap. But as this book is meant to be a sourse book for teachers and not a coherent set of exercises, the author feels this is a minor drawback.
Keywords: Teaching English